Oil, Oil Volatility and Airline Stocks: A Global Analysis - Mohan Nandha; Robert Brooks; Robert Faff (Journal of Accounting and Management Information Systems (JAMIS), 2013)
By selecting a globally representative dataset of airline indices, this study demonstrates that oil price or oil price regimes (delineated by the first gulf war and the 9/11 terror attacks) alone do not have any significant implications for airline stock prices. Overall, these findings are contrary to the general perception that higher oil prices or oil volatility are bad news for the airlines industry. Perhaps airlines are in a better position to estimate their oil risk and take hedging positions as appropriate. However, airlines stocks appear to be significantly prone to the combined effects of oil volatility and oil regimes determined by the globally significant events/ shocks.
Keywords: G15; Q43; 650; Oil price; oil volatility; airlines; gulf war; 9/11 attacks